Digits and narratives of the experience of Italian families facing premature births. (2nd September 2018) - Marini, Maria Giulia; Chesi, Paola; Bruscagnin, Martina; Ceccatelli, Monica; Ruzzon, Elisabetta
Abstract: The objective of the research was to understand the experience of families living a premature birth and to outline the current care plan in Italy. The survey was addressed to 150 parents of children born under the 34 th week of pregnancy. Topics of the investigation were the implications on their family, social and working contexts, determined through a questionnaire enriched by a collection of narratives. Written testimonies were clustered through a Narrative Medicine method and matched with quantitative information. The main respondents were mothers of severe and moderate preterm children. Except for the Kangaroo Care, services were not uniformed amongst the centers and few home care supports resulted available for families. Sixty-seven percent of the mothers could not obtain a prolonged maternity leave and described the impacts on their working activities. Narratives revealed a low level of prevention, information and awareness on the risks of prematurity amongst families, few local networks among Neonatal Intensive Care Unit (NICU) teams, gynecologists and pediatricians, and the shortage of support for parents at work; these actions were collected in a Position Paper. Findings showed the integration between families' coping strategies and the offered care services for preterm births. Narrative tools could represent the bridge between families and health care teams.